2013
DOI: 10.3382/ps.2012-02847
|View full text |Cite
|
Sign up to set email alerts
|

Short-term preservation of fowl sperm in buffered potassium chloride

Abstract: Previous research demonstrated that sperm motility is dependent upon mitochondrial calcium cycling. Thus, sperm are inactivated when extracellular calcium ions are chelated. Mitochondrial calcium cycling, however, is driven by extracellular sodium ions. The hypothesis that sperm inactivation is subject to 2 variables was tested in the present work. Sperm motility was evaluated with computer-assisted sperm motion analysis in the first experiment. Sperm became immotile within minutes when suspended in buffered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The motility in both diluents was also significantly lower post-thawing (P<0.05) than in the fresh condition. The results obtained in this study during the basic sperm evaluation demonstrated that the cryopreservation process affects sperm motility, resulting in a 50% decrease in both diluents; these data are consistent with reports by other authors (Herrera et al 2005, Froman 2013), who report that motility is the only parameter in the basic evaluation of sperm that is affected by the process of freezing bird sperm. The percentage of live sperm did not differ (P>0.05) between the BPSE and Lake diluents, and in fresh (98.0±0.2 and 96.0±1.0) and thawed (95.0±0.5 and 94.0±0.5) semen.…”
Section: Resultssupporting
confidence: 82%
“…The motility in both diluents was also significantly lower post-thawing (P<0.05) than in the fresh condition. The results obtained in this study during the basic sperm evaluation demonstrated that the cryopreservation process affects sperm motility, resulting in a 50% decrease in both diluents; these data are consistent with reports by other authors (Herrera et al 2005, Froman 2013), who report that motility is the only parameter in the basic evaluation of sperm that is affected by the process of freezing bird sperm. The percentage of live sperm did not differ (P>0.05) between the BPSE and Lake diluents, and in fresh (98.0±0.2 and 96.0±1.0) and thawed (95.0±0.5 and 94.0±0.5) semen.…”
Section: Resultssupporting
confidence: 82%
“…This conclusion is valid because fowl sperm propulsion, as measured by either the sperm mobility assay or computer-assisted sperm motion analysis, is absolutely dependent on mitochondrial Ca 2+ cycling. This phenomenon serves to activate phospholipase A2 and thereby provide endogenous long-chain fatty acids for β-oxidation (Froman, 2003(Froman, , 2013Feltmann, 2005, 2010;Froman et al, 2006). In other words, when sperm mitochondria are functional, they then respond to the experimental conditions used.…”
Section: Resultsmentioning
confidence: 99%